2006
DOI: 10.1093/ije/dyl147
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of two studies with contrasting results on the association between statin use and fracture risk: the General Practice Research Database

Abstract: Residual confounding by a matching variable and different definitions of the exposure time window explained differences in results. In case-control studies of drug use and fracture risk, broad matching criteria for age should be avoided and the selection of the time-window for exposure should be carefully considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 23 publications
2
53
1
Order By: Relevance
“…For each of the glucose-lowering agents, biological mechanisms have been postulated for adverse or beneficial cancer effects of these medications. However, biological plausibility may not be sufficient to accept a causal effect, as exemplified by the lack of effects of hormone therapy on cardiovascular disease or statins on fracture, despite apparent biological plausibility [7,32]. Metformin has been reported to decrease cancer risk while insulin may increase it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each of the glucose-lowering agents, biological mechanisms have been postulated for adverse or beneficial cancer effects of these medications. However, biological plausibility may not be sufficient to accept a causal effect, as exemplified by the lack of effects of hormone therapy on cardiovascular disease or statins on fracture, despite apparent biological plausibility [7,32]. Metformin has been reported to decrease cancer risk while insulin may increase it.…”
Section: Discussionmentioning
confidence: 99%
“…Another challenge in research that uses healthcare databases is the complexity of the recorded information and the large number of choices that an investigator needs to make when extracting the information from the database. Studies from different investigators have found discrepant results and reached opposite conclusions when testing similar hypotheses within the same database [7]. Given these potential issues, the first objective of this study was to evaluate whether users of different classes of glucose-lowering agents were comparable with respect to their underlying cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, comorbid conditions registered by the physician were identified using the GPRD Medical Codes for asthma, malabsorption syndromes, inflammatory bowel disease, hypertension, hyperlipidemia (22), ischemic heart disease, cerebrovascular disease (23), chronic obstructive pulmonary disease, chronic renal failure, and cancer. Similarly, use of certain drugs was assessed: antiarrhythmics, anticonvulsants, antidepressants (24), anti-Parkinson's disease agents, anxiolytics, proton-pump inhibitors, hormone replacement therapy (HRT)/selective estrogen receptor modulators (SERMs), and calcium/vitamin D supplements.…”
Section: Methodsmentioning
confidence: 99%
“…However, subtle differences in scientific decisions regarding specific study parameters can have significant impacts on results and interpretation -as was discovered in the controversies over 3 rd generation oral contraceptives and risk of venous thromboembolism or statins and the risk of hip fracture. 17,18 Clarity regarding key operational decisions would have facilitated replication, assessment of validity and earlier understanding of the reasons that studies reported different findings.…”
Section: Introductionmentioning
confidence: 99%